Consumer Behavior in Yogurt Purchase and Consumption (Global Journal of Science Frontier Research, 2020)
In recent years, yogurt has become prevalent in diary fermented food in the market. The trend of yogurt consumption is gradually increasing with customer consciousness on a diet. In the present study, we investigate the yogurt purchase and consumption pattern of people who buy yogurt from PARC Agrotech Company Limited (PATCO) shop in the Nation Agriculture Research Center (NARC). A Chisquare test was applied to assess the yogurt buying and consumption patterns of NARC employees against the outsiders. Besides, the finding showed that out of 27 respondents 17 of them purchased yogurt for others, including friends and relatives. Above findings depicts the importance of yogurt to consumers. Mostly, yogurt was consumed by whole family members comprising of 12 NARC employees and nine outsiders. Yogurt was used throughout the year however; increase consumption of yogurt is observed in summer (67%) as compared to winters and at other times of the year almost (33%). The overall acceptance level of yogurt is high (72.73%) for consumers from outside in contrast with NARC employees (19%). Likewise, in terms of taste, flavor, appearance, price and packing size, most of the buyers outside NARC were highly satisfied with 54.5%, 54.5%, 72.73%, 72.73%, and 54.5% respectively. It is recommended to ensure an adequate supply of yogurt and an improvement in the packing be made.
Keywords: yogurt; consumption; preference; purchase